L'exaltation d'une figure historique au théâtre : le général Spinola dans la comedia El Sitio de Bredá de Calderón - Cyril Merique (Les Cahiers de Framespa, 2015)
Not only was Calderon highly influenced by the events and historical characters of The Surrender of Breda in the writing of his play El Sitio de Breda, but he also resorted to many poetical devices to build up his characters, especially the figure of general Spinola. Assuming that the reconstruction work by the playwright must have contributed to increasing the heroic dimension of Spinola in the play, we shall examine the links between historical discourse and the fictional dimension of the characters as portrayed by the playwright, as well as the way Calderon set up the historical discourse of his characters in order to glorify the magnanimity of the victors.